Development of Metarhizium spp. for the control of locusts and grasshoppers - Lomer, C.J.; Prior, C.; Kooyman, C. (Cambridge University Press, 1997)
Four research programmes are investigating the entomopathogenic fungal genera Metarhizium and Beauveria for locust and grasshopper control in Africa. In the LUBILOSA programme, surveys for pathogen isolates revealed a morphologically distinctive Metarhizium flavoviride Gams and Rozsypal attacking acridoids in West Africa, Madagascar, and elsewhere. Metarhizium anisopliae (Metschnikoff) Sorokin isolates with virulence to acridoids were also obtained, including several from non-orthopteran hosts. Natural epizootics of both genera are rare in acridoid populations, but do occur. A standardized screening method discriminated virulent from non-virulent isolates. The great majority of the most virulent isolates were from the acridoid group of M. flavoviride. A Niger isolate chosen for development from this group had low virulence to honey bees and parasitic Hymenoptera and was not infective to insects in several other orders. Field tests were carried out on formulations of oil mixtures, using ULV application rates of 1–2 L/ha and 2–5 × 1012 conidia per hectare. In preliminary tests, target insects were sprayed successfully in small field arenas and in large cages. Trials in 1993 on variegated grasshopper gave an approx. 90% reduction in field populations after 15 days. Trials on various acridids, predominantly Hieroglyphus daganensis Krauss, in dense grass in northern Benin showed slower mortality, although up to 70% population reduction was achieved. Trials using a vehicle-mounted ULV sprayer (the Ulva-Mast) in open grassland in Niger gave >90% mortality in samples of mixed acridids. In Mali, a Malian isolate of M. flavoviride was shown to be slightly more virulent than the standard Niger isolate; both isolates gave significant population reductions against nymphs of Oedaleus senegalensis Krauss and Kraussella amabile(Krauss) in 1-ha plots. Successful small-scale field trials have also been carried out using the standard M. flavoviride isolate in South Africa against brown locust and in Australia using an Australian isolate against wingless grasshopper. In Mauritania, a trial using the Niger isolate against desert locust nymph bands gave up to 90% mortality in caged samples by day 9 after spraying. The uncaged treated bands were completely destroyed by predators while untreated bands fledged. Oil-based ULV formulations of M. flavoviride are capable of causing high mortality in the field populations of all acridoids against which they have been field tested and show great promise for development as components of IPM strategies for these pests.